Robust Human Machine Interface Based on Head Movements Applied to Assistive Robotics - Elisa Perez; Natalia López; Eugenio Orosco; Carlos Soria; Vicente Mut; Teodiano Freire-Bastos (The Scientific World Journal, 2013)
This paper presents an interface that uses two different sensing techniques and combines both results through a fusion process to obtain the minimum-variance estimator of the orientation of the user’s head. Sensing techniques of the interface are based on an inertial sensor and artificial vision. The orientation of the user’s head is used to steer the navigation of a robotic wheelchair. Also, a control algorithm for assistive technology system is presented. The system is evaluated by four individuals with severe motors disability and a quantitative index was developed, in order to objectively evaluate the performance. The results obtained are promising since most users could perform the proposed tasks with the robotic wheelchair.